Effect of olive by-products feed supplementation on physicochemical and microbiological profile of Provola cheese - Calabrese, Francesco Maria; Russo, Nunziatina; Celano, Giuseppe; Pino, Alessandra; Lopreiato, Vincenzo; Litrenta, Federica; Di Bella, Giuseppa; Liotta, Luigi; De Angelis, Maria; Caggia, Cinzia; Randazzo, Cinzia L. (Frontiers in Microbiology, 2023)
With the purpose to evaluate the effects of dietary olive cake, a source of bioactive phenolic compounds, as feed supplementation of lactating dairy cows on fatty acid composition, volatile organic compounds, and microbiological profiles of Provola cheese, we performed a two-arm study where control and experimental administered cows derived dairy have been compared. Looking at the physicochemical variable’s profiles, a higher content of unsaturated fatty acids, polyunsaturated fatty acid, and conjugated linoleic acids as well of proteins were observed in experimental cheese samples, indicating the beneficial effect of dietary supplementation. Furthermore, based on volatilome composition, a clear cluster separation between control and experimental cheeses was obtained, mainly related to terpenes degradation, able of influencing their aroma and taste. Microbiological results showed a decrease of some spoilage related microbial groups in experimental cheeses, probably due to the inhibitory effect exerted by polyphenols compounds, that contrarily did not affect the core taxa of all cheese samples. This paper confirmed the promising utilization of olive by-product in farming practices to obtain more sustainable and safe dairy food products with lower environmental impact, mainly in Sicily and Mediterranean area, where waste disposal poses serious environmental and economic problems.